PENINGKATAN KEMAMPUAN BERBICARA SISWA KELAS V SD NEGERI MODEL TERPADU MADANI DENGAN PENDEKATAN SCIENTIFIC - Rumondor, Paul (BAHASANTODEA, 2016)
On the observation, it was found that most students of thr grade V didi not have good ability in speaking Indonesia language. When Indonesia language is used orally, the students tend to use it incorrectly and unclearly. The results in different meaning such as â€œlaguâ€ and â€œraguâ€ and interupted use when both asking and responding questions. This research aimed at (1) finding out and analysing the improvement of studentsâ€™ speaking ability of the grade V of SDN model Terpadu Madani Palu through scientific approach, and (2) finding out the use of scientific approach in improving the studentsâ€™ speaking ability of grade V of SDN Model Terpadu Madani. This was classroom action research and the subjects were grade V students of SDN Model Terpadu Madani. This research was conducted in two cycles. Each cycle went through observing, asking, collecting and processing information, drawing conclusion, and recomending. The reseach showed that the use of scientific approach can improve the studentsâ€™ ability in speaking. Based on the result in Cycle I, there was an average improvement in some aspects: pronu ciation 2.59; structure, 2.64; vocabulary, 2.59; patience, 2.82; voice volume, 2.68; fluency, 2.64; and comprehension, 2.59. The studentsâ€™ speaking ability was 2.65. In cycle I, the problem was the studentsâ€™ activity was not optimal. The effort was to improve the instructional scenario and encourage the students. Icycle II, the results are pronunciation, 3.59; structure, 3.41; vocabulary, 3.64; patience, 3.50;,voice volume, 3.64; fluency, 3.50 and comprehension, 3.59. The studentsâ€™ speaking ability has reached 3.55. This result indicates that use of scientific approach can improve the studentâ€™ speaking ability of grade V of SDN Model Terpadu Madani.